2021
DOI: 10.3390/biochem1030017
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Antioxidant Activities of the Twigs of Andrograhis paniculata on Streptozotocin-Induced Diabetic Male Rats

Abstract: Background: Diabetes is associated with chronic hyperglycaemia, long-term damage, dysfunction, and organ failure. This study aims to evaluate the antidiabetic activity of the twigs of Andrographis paniculata and its toxicological markers on Streptozotocin (STZ)-induced diabetic Albino rats. Methods: A total of thirty rats were randomly divided into five groups of six animals each. Non-diabetic animals were treated with distilled water as non-diabetic sham control group 1, while diabetic animals (group 2, 3, 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
(21 reference statements)
1
7
0
Order By: Relevance
“…These findings are consistent with prior research that found flavonoids to have hepatorenal protective properties [ 29 ]. Rosinidin molecules significantly suppress amylase enzymes, signifying anti-diabetic effects; this is consistent with prior studies on other flavonoids [ 30 , 31 , 32 ]. Furthermore, rosinidin protects vital tissues including the pancreas, thereby lowering risks of diabetes-related complications.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with prior research that found flavonoids to have hepatorenal protective properties [ 29 ]. Rosinidin molecules significantly suppress amylase enzymes, signifying anti-diabetic effects; this is consistent with prior studies on other flavonoids [ 30 , 31 , 32 ]. Furthermore, rosinidin protects vital tissues including the pancreas, thereby lowering risks of diabetes-related complications.…”
Section: Discussionsupporting
confidence: 91%
“…Medicinal plants have therapeutic agents as they contain phytochemicals with vast medicinal potential which are employed in the prevention, maintenance, and treatment of diseases (4). Herbs are regarded as the major source of pharmaceuticals in the development of drugs and pharmaceuticals used in the treatment of human diseases as a result of the diversity of the phytochemicals contained in them (5).…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated serum creatinine and BUN levels (Table 2). Creatinine, a major product of muscle metabolism, is excreted by the kidney and serves as an important indicator of renal function [41]. Elevated creatinine levels are often associated with renal failure.…”
Section: Discussionmentioning
confidence: 99%